THE ADOPTION OF THE ADDIE MODEL IN DESIGNING AN INSTRUCTIONAL MODULE: THE CASE OF MALAY LANGUAGE REMOVE STUDENTS - Suratnu, Roslina (IJIET (International Journal of Indonesian Education and Teaching), 2023)
This study aims to examine the process involved in designing an instructional module based on the ADDIE model which was developed by Dick Carey (1996). An instructional module is one of the main tools in the teaching and learning (TL) process of a subject. Therefore, the design of modules needs to be based on an instructional model that details the phases of the process carefully and systematically. Thus, this study explores the use of the ADDIE model in designing an instructional module for the subject of the Malay language at the remedial level.  The ADDIE model consists of five phases: namely analysis, design, development, implementation, and evaluation. The use of the ADDIE model in designing the instructional module has helped in meeting the objectives of teaching and learning as the model uses a systematic approach that fulfills the needs of students. It is hoped that this module can help improve the mastery of basic reading and writing skills for students.